Appropriation, Activation and Acceleration: The Escalatory Logics of Capitalist Modernity and the Crises of Dynamic Stabilization. (January 2017) - Rosa, Hartmut; Dörre, Klaus; Lessenich, Stephan
The paper starts by identifying dynamic stabilization as a defining feature of modern societies. This term refers to the fact that such a society requires (material) growth, (technological) augmentation and high rates of (cultural) innovation in order to reproduce its structure and to preserve the socioeconomic and political status quo. The subsequent sections explore the mechanisms and consequences of this mode of social reproduction, proceeding in three steps. First, three key aspects or 'motors' of dynamization are identified, namely the mechanisms of (socio-economic) appropriation, (socio-cultural) acceleration and (socio-political) activation . In the second step, we argue that this 'Triple-A-Mode' of dynamic stabilization necessarily entails a logic of incessant escalation which eventually threatens to undermine itself, leading to a multifaceted process of destabilization. Unmistakable signs of this can be seen in the current financial, democratic, ecological and psychosocial crises. The third and last part briefly and very preliminarily sketches out the possible contours of a 'post-growth' society which could move beyond the current mode of dynamic stabilization.